Comparative Study of Al-Ghazali and Ibn Arabi's Theodicy Thoughts About Divine Love - Syah, Yoshy Hendra Hardiyan; Kuswana, Dadang; Qomaruzzaman, Bambang (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
This research discusses the Covid-19 virus as an example of a case of suffering from the problematics of Theodicy, because Covid-19 has claimed lives, suffered economically, socially and academically, so that it appears that God is not all-just, not all-loving and not all-merciful. This research is qualitative research using descriptive analysis methods and comparative methods. This type of research is a literature review (Library Research) which uses a philosophical approach, and uses theodicy theory in the Covid-19 case. Primary data sources in this research include the works of Ibn Arabi, namely